Integrating the Computer in the Classroom: An Approach in Auditing. - Dock, V. Thomas; Guy, Dan M.; Williams, Doyle Z. (The Accounting Review, 1974)
Abstract The article discusses integrating computer-oriented material into accounting courses, including the auditing course. An auditor's responsibilities within an organization force a need to work with the computer in new and changing ways, and this element should be incorporated into auditing instruction. Because of their increasing ease of use, usage of generalized computer audit systems (GCAS) has increased dramatically. An auditing student should understand the fundamental concepts of a GCAS and the potential of this new tool for the auditor.